High temperature steam electrolytic cell and manufacturing method thereof
A composite support layer of nickel oxide and gadolinium-doped ceria with 30 μm crystal particles addresses the balance of mechanical strength and gas permeability in high-temperature water vapor electrolytic cells, enhancing durability and electrolysis efficiency.
Patent Information
- Application Number
- JP2023116666
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-30
AI Technical Summary
Existing high-temperature water vapor electrolytic cells face challenges in balancing mechanical strength and gas permeability due to the inherent weaknesses of the support layer, leading to potential destruction and reduced performance.
The use of a support layer composed of a composite of nickel oxide (NIO) and gadolinium-doped ceria (GDC) with crystal particles of 30 μm or more, enhancing mechanical strength while maintaining gas permeability, thereby reducing crack propagation and improving the overall durability of the electrolytic cell.
The solution effectively enhances the mechanical reliability of the electrolytic cell by suppressing crack progression and maintaining structural integrity, ensuring efficient electrolysis of water vapor into hydrogen and oxygen.
Smart Images

Figure 2025014253000001_ABST
Abstract
Description
[Technical field]
[0001] SUMMARY OF THE DISCLOSURE Embodiments of the present invention relate to high temperature steam electrolysis cells and methods of making same. [Background technology]
[0002] In recent years, the introduction of renewable energies such as solar, wind and geothermal energy has been promoted from the viewpoints of environmental issues such as the depletion of fossil fuels and global warming due to the release of carbon dioxide into the atmosphere, as well as energy security. In addition, hydrogen energy has attracted attention as a secondary energy source from the viewpoints of storage and transportation. Hydrogen energy is expected to be applied to, for example, fuel cell vehicles, and there is a demand for low-cost production and storage of high-quality hydrogen.
[0003] Currently, the mainstream method of producing hydrogen is to produce it by reforming fossil fuels from the standpoint of cost and technology. However, producing hydrogen by reforming fossil fuels inevitably generates carbon dioxide during the production process. In contrast, it is known that producing hydrogen using renewable energy and water as a raw material does not generate carbon dioxide and has a small environmental impact. Methods for producing hydrogen by electrolyzing water or water vapor include the PEM type, which uses a solid polymer electrolyte membrane (PEM), and the SOEC type, which uses a solid oxide electrolysis cell (SOEC). Among these, the SOEC type is expected to be a hydrogen production method of the future because, in principle, it requires less electricity to produce hydrogen.
[0004] SOECs used in the electrolysis of water vapor to produce hydrogen are composed of a hydrogen electrode support layer that passes electrons, a hydrogen electrode (active layer) that electrolyzes water, a solid oxide electrolyte layer that conducts oxygen ions, and an oxygen electrode that bonds the oxygen ions to form oxygen molecules. The electrolyte has oxygen ion conductivity and plays a role in separating hydrogen gas and oxygen gas. The support layer, which has the largest volume in the cell, is required to pass electrons as well as to have gas permeability to supply water vapor to the active layer and strength to maintain the shape of the electrolysis cell. A porous layer is used for the support layer to achieve gas permeability. The support layer is required to have the contradictory properties of being a porous layer that has pores that are considered defects and to achieve high strength.
[0005] In other words, the support layer of an SOEC is required to have mechanical reliability such as strength, but also gas permeability, and therefore has pores that can be the starting point of breakdown, making it prone to low strength.Thus, the support layer is required to have both mechanical reliability and gas permeability, but there is a problem in that in order to ensure the electrolysis cell performance of gas permeability, the mechanical reliability based on the porous layer must be kept low. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2021-147664 A [Patent Document 2] Patent Publication No. 2022-180156 [Patent Document 3] Patent Publication No. 2021-096432 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a high-temperature steam electrolysis cell that is provided with a support layer having increased strength while maintaining the gas permeability required for an electrolysis cell, thereby enabling both the steam electrolysis reaction and mechanical strength to be achieved, and a method for producing the same. [Means for solving the problem]
[0008] A high-temperature steam electrolysis cell according to an embodiment includes a gas-permeable support layer, a hydrogen electrode provided on the support layer, the hydrogen electrode having gas permeability and capable of electrolyzing steam flowing therein into oxygen ions and hydrogen, a solid oxide electrolyte layer capable of conducting the oxygen ions generated at the hydrogen electrode, and an oxygen electrode having gas permeability and capable of generating oxygen molecules from the oxygen ions arriving from the solid oxide electrolyte layer. In the high-temperature steam electrolysis cell according to an embodiment, the support layer contains a composite of nickel oxide and gadolinium-doped ceria as a main component, and nickel oxide particles having a crystal grain size of 30 μm or more are present in the composite. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a cross-sectional view showing a high temperature steam electrolysis cell according to an embodiment. [Diagram 2] 1 shows SEM images showing the progress of cracks in a conventional NiO-GDC sintered composite. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, high-temperature steam electrolysis cells according to embodiments will be described with reference to the drawings. In each of the embodiments described below, substantially identical components are denoted by the same reference numerals, and some of the descriptions thereof may be omitted. The drawings are schematic, and the relationship between thickness and planar dimensions, the thickness ratio of each part, etc. may differ from the actual ones.
[0011] FIG 1 shows a cross section of a high-temperature steam electrolysis cell according to an embodiment. The high-temperature steam electrolysis cell 1 shown in FIG 1 is an SOEC that generates hydrogen and oxygen by electrolyzing high-temperature steam, and includes a support layer 2, a hydrogen electrode 3, a solid oxide electrolyte layer 4, an intermediate layer 5, and an oxygen electrode 6. The intermediate layer 5 is provided as necessary. Here, a flat-plate type SOEC 1 is shown, but the electrolysis cell 1 may be a cylindrical type or other type that is not flat, as long as it has a layered structure of the support layer 2, the hydrogen electrode, the solid oxide electrolyte layer 4, the intermediate layer 5, and the oxygen electrode 6. The intermediate layer 5 is provided as necessary, and the electrolysis cell 1 does not need to have the intermediate layer 5.
[0012] The support layer 2 is a strength member that mainly provides the strength of the electrolysis cell 1, and is made of a gas-permeable porous sintered body, and has water vapor passages through which water vapor can flow. The support layer 2 contains a composite of nickel oxide (NiO) and gadolinium doped ceria (GDC (Gadolinia Doped Ceria (CeO2): GDC) as a main component, and is provided with a porous sintered layer of such a composite. The porous sintered body as the support layer 2 has a porosity of, for example, about 30% or more and 50% or less. The specific configuration of the porous sintered body as the support layer 2, such as the crystal grain size, will be described in detail later.
[0013] The hydrogen electrode 3 is provided on the support layer 2. The hydrogen electrode 3 is composed of a porous layer made of a hydrogen electrode active material, and specifically, has gas permeability due to the skeleton of a network structure. The hydrogen electrode 3 has open pores at least partially surrounded by the skeleton of a network structure inside, and can electrolyze water vapor that flows into the open pores into oxygen ions and hydrogen. The hydrogen electrode 3 is made of, for example, a composite of NiO and gadolinium solid-doped ceria (GDC). In addition, a composite of an oxide of Co, Fe, Cu, Ru, or the like, and an oxide of a rare earth element or zirconia stabilized with a rare earth element may be applied to the hydrogen electrode 3. The water vapor that flows into the open pores in the hydrogen electrode 3 from the water vapor passage of the support layer 2 is mainly electrolyzed into oxygen ions and hydrogen in the hydrogen electrode (active layer) 3. Hydrogen gas (H2) generated by electrolysis is led to the outside from a gas flow passage (not shown) and, for example, stored. The generated oxygen ions are conducted into the solid oxide electrolyte layer 4.
[0014] One surface of the solid oxide electrolyte layer 4 is laminated with the hydrogen electrode 3, and the other surface is laminated with the oxygen electrode 6 via an intermediate layer 5, or directly with the oxygen electrode 6. The solid oxide electrolyte layer 4 is made of a dense solid oxide electrolyte, and is an ion conductor that passes ions such as oxygen ions but does not pass electricity. For the solid oxide electrolyte layer 4, stabilized zirconia in which a stabilizer made of an oxide of a rare earth element such as Y, Sc, Ce, Gd, or Sm is dissolved, typically yttria-stabilized zirconia (YSZ) or ceria-stabilized zirconia (CSZ), or a composite of these can be used.
[0015] The oxygen electrode 6 is made of an oxygen electrode active material and is composed of a porous body having gas diffusibility and electronic conductivity. The oxygen ions (O 2- ) and the electrons (e -) to generate oxygen molecules (O2). The generated oxygen gas (O2) is discharged to the outside through a gas flow passage (not shown) and is stored, for example, as required. The oxygen electrode 6 is made of a porous sintered body containing an oxide having a perovskite structure represented by ABO3 (hereinafter, referred to as perovskite oxide). The oxygen electrode 6 is made of a porous sintered body containing an oxide having a perovskite structure represented by ABO3 (hereinafter, referred to as perovskite oxide). 1-x A x B 1-y C y O 3-δ (wherein R is a rare earth element such as La, A is an alkaline earth element such as Sr, Ca, Ba, B and C are metal elements such as Cr, Mn, Co, Fe, Ni, and x, y and δ are atomic ratios that satisfy 0≦x≦1, 0≦y≦1, and 0≦δ≦1.) A typical example of the oxygen electrode 6 is a perovskite oxide represented by the formula: 1-x Sr x )(Co 1-y Fe y )O 3-δ (LSCF) is one example.
[0016] The intermediate layer 5 is disposed between the solid oxide electrolyte layer 4 and the oxygen electrode 6 as required, and is a dense reaction prevention layer that prevents diffusion and reaction of elements between the solid oxide electrolyte layer 4 and the oxygen electrode 6. The SOEC 1 of the embodiment is configured by sequentially stacking the support layer 2, the hydrogen electrode 3, the solid oxide electrolyte layer 4, the intermediate layer 5 as required, and the oxygen electrode 6. More specifically, a thin film of the hydrogen electrode 3 is formed on the support layer 2, and a thin film of the solid oxide electrolyte layer 4 is further formed on the hydrogen electrode 3. The SOEC 1 is further configured by forming a thin film of the intermediate layer 5 and the oxygen electrode 6 on the solid oxide electrolyte layer 4. Regarding the thickness of each component, for example, the support layer 2 has a thickness of 500 μm or more and 800 μm or less, the hydrogen electrode 3 has a thickness of 30 μm or more and 50 μm or less, the solid oxide electrolyte layer 4 has a thickness of 10 μm or more and 15 μm or less, the intermediate layer 5 has a thickness of 5 μm or more and 10 μm or less, and the oxygen electrode 6 has a thickness of 30 μm or more and 50 μm or less.
[0017] Next, the support layer 2 will be described in detail. The high-temperature steam electrolysis cell 1 is manufactured, for example, by adding a binder, a pore-forming agent, and a solvent to a raw material powder to form a slurry, forming the slurry into a sheet, laminating, and pressing the slurry into a compact, and then subjecting the compact to a debinding step (a binder removal process) and a sintering step. The compact of the support layer 2 may be produced by press molding after adding a binder, a pore-forming agent, and the like to the raw material powder. The pore-forming agent added to make the support layer 2 porous is thermally decomposed and removed in the debinding step, and the remaining holes remain even after sintering, realizing the porousness of the support layer 2. In general, the porosity of the support layer 2 is around 40% (for example, about 30% to 50%), and the high porosity allows the gas permeability to be exhibited.
[0018] However, when a load is applied to the porous sintered body as described above, stress is generated in the matrix located around the pores according to its shape. If the generated stress becomes higher than the rupture strength of the matrix, cracks are generated, and the cracks propagate, causing the destruction of the support layer 2 and eventually the large-scale destruction of the entire electrolytic cell 1. Therefore, it is important to control the pore morphology, such as the diameter and shape of the pores, and to suppress the propagation of the cracks. Spherical particles, which are least likely to cause stress concentration, are often used as the pore-forming agent. Ceramics (sintered bodies), which are brittle materials, are required to have high strength for ease of handling and setting. If the Young's modulus is high, even a slight deformation generates high stress, which easily destroys the material, so a low Young's modulus is preferable.
[0019] Therefore, for the support layer 2 in the embodiment, a sintered body of a composite of NiO and GDC, which is effective as a constituent material of the support layer 2 in contact with the hydrogen electrode 3, is used, and the crystal grain size of some of the NiO particles in the composite is set to 30 μm or more. As shown in the enlarged photograph (SEM image) of a conventional NiO-GDC composite sintered body in FIG. 2, a crack occurring in the composite as a porous sintered body mainly progresses along the crystal sphere boundary. If NiO particles with a crystal grain size of 30 μm or more are present in such a crack progress region, the crack progress energy is reduced by the NiO particles. In this way, by reducing the crack progress energy by NiO particles with a crystal grain size of 30 μm or more, it is possible to suppress the occurrence and progress of microcracks due to crack branching. Alternatively, even if microcracks occur due to crack branching, the crack energy is reduced by branching the cracks, so that it is possible to suppress the crack progress in the entire support layer 2 and the resulting destruction of the support layer 2.
[0020] In the NiO particles present in the compound sintered body constituting the support layer 2, the ratio (volume ratio) of NiO particles having a crystal grain size of 30 μm or more is preferably 5 vol% or more, and more preferably 10 vol% or more. If the ratio of NiO particles having a crystal grain size of 30 μm or more is less than 5 vol%, the above-mentioned effect of reducing the crack propagation energy may not be sufficiently obtained. If the ratio of NiO particles having a crystal grain size of 30 μm or more is 10 vol% or more, the effect of reducing the crack propagation energy can be obtained more effectively. However, if the ratio of NiO particles having a crystal grain size of 30 μm or more is too high, the strength of the compound sintered body as a constituent material of the support layer 2 is likely to decrease, and the handleability and cell strength of the support layer 2 and the electrolysis cell 1 having the same are reduced. Therefore, it is preferable that the ratio of NiO particles having a crystal grain size of 30 μm or more is 30 vol% or less.
[0021] That is, by containing 30 volume % or less NiO particles with a crystal grain size of 30 μm or more and the rest being NiO particles with a crystal grain size of less than 30 μm, it is possible to reduce the propagation energy of cracks propagating in the support layer 2 while maintaining the strength of the support layer 2, and to suppress destruction of the support layer 2 due to cracks. Furthermore, it is preferable that the average grain size of the GDC particles in the compound sintered body constituting the support layer 2 is 20 μm or less. This can increase the strength of the support layer 2. It is preferable that the average grain size of the entire support layer 2, which is mainly composed of NiO particles and GDC particles, is 10 μm or more and 60 μm or less. This can also increase the strength of the support layer 2.
[0022] In the support layer 2 composed of the above-mentioned composite sintered body of NiO particles and GDC particles, the average particle size of NiO particles, the average particle size of GDC particles, and the average particle size of the entire support layer 2 are measured in accordance with the ASTM standard (ASTM112-82). For example, a part of the support layer 2 is magnified and imaged with a scanning electron microscope (SEM). The composition of the crystal grains is confirmed by energy-dispersive X-ray spectroscopy (EDS) for the same location as the imaged location of the SEM image, and it is determined whether the grains are NiO particles or GDC particles. Based on such a determination result, image analysis is performed only on the NiO particles in the SEM image, and the ratio of NiO particles with a crystal grain size of 30 μm or more and the average grain size of the NiO particles are measured. In the same manner, the average grain size of the GDC particles and the average grain size of all crystal grains in the composite sintered body are measured. The volume ratio of NiO particles with a crystal grain size of 30 μm or more is obtained as being equivalent to the area ratio in the SEM image.
[0023] The support layer 2 composed of the composite sintered body of NiO particles and GDC particles as described above can be obtained, for example, as follows. That is, NiO powder and GDC powder are mixed, for example, in a mass ratio range of 5:5 to 7:3. At this time, the NiO powder is used by mixing a first powder having an average particle size of 0.2 to 2.0 μm and a second powder having an average particle size of 30 to 50 μm, for example, in a mass ratio range of 99:1 to 60:40. Such a mixed powder of NiO powder (first powder and second powder) and GDC powder is used as a raw material powder, to which a binder and a pore-forming agent are added, and further a solvent is added and mixed to prepare a slurry. The slurry thus prepared is formed into a sheet of a required thickness to prepare a sheet for the support layer. A porous sintered body can be obtained by forming a slurry for forming the hydrogen electrode 3 and a slurry for forming the electrolyte layer 4 on such a sheet for the support layer or on the sheet for the support layer in order and thermocompressing the slurry, and then performing a degreasing process and a sintering process.
[0024] The manufacturing method of the high temperature steam electrolysis cell 1 of the embodiment is not particularly limited, but can be, for example, as follows. First, NiO powder and GDC powder are mixed in the above-mentioned ratio to prepare a raw material powder. In this case, it is preferable to use the NiO powder by mixing the first powder having an average particle size of 0.2 to 2.0 μm and the second powder having an average particle size of 30 to 50 μm in a mass ratio of, for example, 99:1 to 60:40. The average particle size of the GDC powder is not necessarily limited, but it is preferable that the average particle size is 0.1 μm or more and 30 μm or less.
[0025] Next, a binder and a pore-forming agent are added to the raw material powder, and a solvent is further added as necessary to mix them to prepare a raw material slurry. The raw material slurry is formed into a sheet to produce a sheet. Next, a slurry for forming the hydrogen electrode 3 and a slurry for forming the solid oxide electrolyte layer 4 are formed into sheets on the obtained sheet in order to produce a laminated compact. The laminated compact is subjected to the steps of thermocompression bonding, degreasing, and sintering to produce a porous laminated sintered body. The high-temperature steam electrolysis cell 1 is obtained by carrying out the steps of forming and baking the materials for forming the intermediate layer 5 and the oxygen electrode 6 on the laminated sintered body. Note that each of these constituent layers may be degreased and sintered separately. EXAMPLES
[0026] Next, specific examples of the electrolytic cell according to the embodiment and the evaluation results thereof will be described.
[0027] (Example 1, Comparative Example 1) In manufacturing the high-temperature steam electrolysis cell, first, nickel oxide (NiO) powder and gadolinium-doped ceria (GDC) powder were prepared as raw materials for the support layer. The NiO powder was prepared by mixing a first powder having an average particle size of 0.6 μm and a second powder having an average particle size of 30 μm in a mass ratio of 99:1 to 60:40, and the total average particle size was adjusted to 0.2 to 30 μm. The GDC powder had an average particle size of 10 to 60 μm. The NiO powder and GDC were mixed in a mass ratio of 6:4 to prepare the raw material powders of Examples 1 to 5. In Comparative Example 1, the raw material powder was prepared in the same manner as in the Examples, except that only the first powder having an average particle size of 0.6 μm was used for the NiO powder, and the second powder having a relatively large particle size was not used.
[0028] 100 parts by mass of each of the above raw material powders were mixed with 10 parts by mass of polyvinyl acetal resin as a binder, 5 parts by mass of polyvinyl alcohol resin with an average particle size of 1 μm as a pore-forming agent, and ethanol as a solvent, and pot-mixed for 24 hours to prepare slurries. Each of the slurries thus prepared was formed into a sheet having a thickness of 0.6 mm to prepare a sheet for the support layer.
[0029] Next, NiO-GDC-based slurry was formed on each of the above-mentioned sheets as a material for forming the hydrogen electrode active layer. For the electrolyte layer, a sheet of yttria-stabilized zirconia (YSZ) slurry was screen-printed in a sheet shape with a thickness of 0.015 mm using a sheet of a polyethylene terephthalate (PET) film with a silicone coating. Furthermore, the prepared support layer and sheets for the hydrogen electrode active layer and the sheet for the electrolyte layer were thermocompressed at a temperature of 70°C and a pressure of 15 MPa for 20 minutes to form a laminated molded body, and then degreasing was performed at 400°C for 2 hours. Furthermore, the degreased body was sintered at 1400°C for 2 hours to obtain a sintered body. The atmosphere during degreasing and sintering was air, and the heating rate was 10°C / hour. LSCF was screen-printed as an oxygen electrode on the electrolyte side of the sintered body obtained in this way, and then the oxygen electrode was formed by firing and baking at 1000°C for 1 hour.
[0030] In this way, a 50×50 mm sintered body for an electrolysis cell was obtained. In such a sintered body, the ratio (volume ratio) of NiO particles having a crystal grain size of 30 μm or more, the average grain size of NiO particles, the average grain size of GDC particles, and the average grain size of all the constituent crystal grains of the sintered body were measured according to the above-mentioned method. Furthermore, using such a sintered body, a three-point bending test was performed at a load application rate of 0.5 mm / min to measure the fracture strength of each. Table 1 shows the relationship between the ratio (volume ratio) of NiO particles having a crystal grain size of 30 μm or more and the three-point bending strength of the sintered body. The three-point bending strength is the result of performing a three-point bending test at a load application rate of 0.5 mm / min. Table 1 shows the measurement results of the three-point bending strength of sintered bodies produced by changing the mixing ratio of the first powder with an average grain size of NiO powder of 0.6 μm and the second powder with an average grain size of 30 μm. The average grain size of GDC is 5 μm.
[0031] [Table 1]
[0032] As shown in Table 1, the fracture strength of the sintered body can be increased by having NiO particles with a crystal grain size of 30 μm or more in the sintered body. Furthermore, in order to more effectively increase the fracture strength of the sintered body, it is preferable that the ratio of NiO particles with a crystal grain size of 30 μm or more is 5 volume % or more, and further 10 volume % or more. Table 2 shows the relationship between the average grain size of NiO particles and the average grain size of GDC particles and the three-point bending strength of the sintered body.
[0033] [Table 2]
[0034] As shown in Table 2, it is preferable that the average particle size of the GDC particles is 20 μm or more. This can further increase the fracture strength of the sintered body. From the results of these examples, it is possible to provide an electrolysis cell with improved mechanical reliability.
[0035] Example 2 An electrolysis cell was produced in the same manner as in Example 1, except that the molding method of the support layer in Example 1 was changed from sheet molding to press molding. It was confirmed that in Example 2 as well, good results were obtained, similar to Example 1.
[0036] The configurations of the above-mentioned embodiments can be applied in combination with each other, and some of them can be replaced. Although several embodiments of the present invention have been described here, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. These embodiments and their modifications are included in the scope and gist of the invention, and are also included in the scope of the invention and its equivalents described in the claims. [Explanation of symbols]
[0037] 1...high-temperature steam electrolysis cell, 2...support layer, 3...hydrogen electrode, 4...solid oxide electrolyte layer, 5...intermediate layer, 6...oxygen electrode.
Claims
1. A gas permeable support layer; a hydrogen electrode provided on the support layer, having gas permeability and capable of electrolyzing water vapor that has flowed into the hydrogen electrode into oxygen ions and hydrogen; a solid oxide electrolyte layer capable of conducting the oxygen ions generated at the hydrogen electrode; an oxygen electrode having gas permeability and capable of generating oxygen molecules from the oxygen ions arriving from the solid oxide electrolyte layer; The support layer comprises a composite of nickel oxide and gadolinium-doped ceria as a main component, and nickel oxide particles having a crystal grain size of 30 μm or more are present in the composite.
2. 2. The high-temperature steam electrolysis cell according to claim 1, wherein the nickel oxide particles having a crystal grain size of 30 μm or more are present in the composite at 10% by volume or more.
3. 2. The high-temperature steam electrolysis cell according to claim 1, wherein the average particle size of the gadolinium-doped ceria particles present in the composite is 20 μm or less.
4. 2. A method for producing a high temperature steam electrolysis cell according to claim 1, comprising the steps of: a step of mixing, as the nickel oxide powder, a first powder having an average particle size of 2.0 μm or less and a second powder having an average particle size of 30 μm or more in a mass ratio of 99:1 to 60:40; a step of preparing a raw material powder by mixing a mixed powder of the first powder and the second powder as the nickel oxide powder and a powder of the gadolinium-doped ceria; adding a binder and a pore-forming agent to the raw material powder to prepare a sintered raw material; A step of forming the sintered body raw material into a sheet shape to obtain a molded body; A step of degreasing the molded body to obtain a degreased body; sintering the degreased body to obtain a porous sintered layer as the support layer; A method for manufacturing a high-temperature steam electrolysis cell comprising:
5. 5. The method for producing a high-temperature steam electrolysis cell according to claim 4, wherein the raw material powder contains the nickel oxide powder and the gadolinium-doped ceria powder in a mass ratio of 5:5 to 7:
3.
6. The method for producing a high-temperature steam electrolysis cell according to claim 4, further comprising the steps of: adding a solvent to the sintered body raw material to prepare a raw material slurry; and forming the raw material slurry into a sheet to obtain the green body.
7. 7. The method for producing a high-temperature steam electrolysis cell according to claim 6, wherein the green body forming step comprises: forming a hydrogen electrode formation slurry into a sheet on the green body produced by sheet forming the raw material slurry to produce a laminated green body; and laminating a formation sheet for the solid oxide electrolyte layer on the laminated green body, and the degreasing step and the sintering step are performed on the laminated green body on which the formation sheet for the solid oxide electrolyte layer is laminated.
Citation Information
Patent Citations
Anode supporting substrate for solid oxide fuel cell, and its manufacturing method
JP2004296093A
Unit cell of fuel cell, cell stack device, fuel cell module, and fuel cell device
JP2011096432A
High-temperature steam electrolytic hydrogen production cell and manufacturing method for high-temperature steam electrolytic hydrogen production cell
JP2021147664A
Production method of high temperature steam electrolytic cell, production method of hydrogen electrode layer for high temperature steam electrolytic cell, and production method of solid oxide electrochemical cell
JP2021155852A
Image forming apparatus, image forming method, and program
JP2021096432A